2001
DOI: 10.1001/archpsyc.58.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Systematic Depression Treatment for High Utilizers of General Medical Care

Abstract: Among high utilizers of medical care, systematic identification and treatment of depression produce significant and sustained improvements in clinical outcomes as well as significant increases in health services costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
153
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(159 citation statements)
references
References 40 publications
3
153
2
1
Order By: Relevance
“…The potential benefit of calculating depression indicators for the population in need is that the resulting indicator could motivate employer purchasers to support cost-effective quality improvement initiatives which modestly increase health care expenditures (Rost, Pyne, Dickinson, & LoSasso. The cost-effectiveness of ongoing management for primary care major depression, 2005) (Schoenbaum et al, 2001;Lave, Frank, Schulberg, & Kamlet, 1998;Simon et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…The potential benefit of calculating depression indicators for the population in need is that the resulting indicator could motivate employer purchasers to support cost-effective quality improvement initiatives which modestly increase health care expenditures (Rost, Pyne, Dickinson, & LoSasso. The cost-effectiveness of ongoing management for primary care major depression, 2005) (Schoenbaum et al, 2001;Lave, Frank, Schulberg, & Kamlet, 1998;Simon et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…8 Only one study examined frequent attendance over 2 years; 10,11 all others included 1-year frequent attenders. [24][25][26] Although none of the studies found evidence that it is possible to influence healthcare utilisation by frequent attenders, the one that included frequent attenders over 2 years did find evidence that treatment of major depressive disorder in a subgroup of depressed frequent attenders improved their symptoms and quality of life.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…8 No study showed convincing evidence that an intervention improves quality of life or morbidity of frequent-attending primary care patients, although an effect might exist in a subgroup of depressed frequent attenders. [9][10][11] For this subgroup, one trial concluded that, in the year following the intervention, patients in the intervention group had a mean of 47 more depression-free days (5% confidence interval [CI] = 27 to 68) than patients with depression who received no intervention. 11 There is no evidence that it is possible to influence healthcare utilisation of frequent attenders.…”
Section: Introductionmentioning
confidence: 99%
“…15 The US Preventive Services Task Force "recommends screening adults for depression in clinical practices that have systems in place to assure accurate diagnosis, effective treatment, and follow-up" with a grade B recommendation, 16 as such systems have been demonstrated to improve health status and, in some instances, to reduce health care costs. [17][18][19][20] There is a remarkable paucity of information about patients' understanding of depression and its treatment options, and the role patients play in choosing treatment options. The very limited evidence available suggests quite modest benefits of patient education materials for depression in isolation from more comprehensive interventions.…”
mentioning
confidence: 99%